2022
DOI: 10.33603/signal.v10i2.7240
|View full text |Cite
|
Sign up to set email alerts
|

TRANSFORMASI MEDIA CETAK KE PLATFORM DIGITAL (Analisis Mediamorfosis Harian SOLOPOS)

Abstract: Terjadinya peningkatan jumlah pengguna media berita online dalam lima tahun terakhir dibanding dengan pengguna media berita konvensional memaksa media cetak untuk melakukan transformasi ke platform digital. Salah satu media yang telah melakukan transformasi media (mediamorfosis) adalah Harian SOLOPOS yang terbit di Solo, Jawa Tengah. Tujuan penelitian ini adalah pertama, untuk mengetahui dan mendeskripsikan mediamorfosis Harian SOLOPOS ke platform digital; dan kedua, untuk menemukan dan menjelaskan model perub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Based on this, there is a tendency for communication students to get more information through social media than mass media; they even read information through social media more often than mass media which they rarely use. Suryawati & Alam (2022) research suggested that integrated Social media would be able to add insight as social media usually have the latest "news or issues." Through social media, a new way of life enables multiple perspectives, as marginalized people now have a platform to discuss their needs and life experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, there is a tendency for communication students to get more information through social media than mass media; they even read information through social media more often than mass media which they rarely use. Suryawati & Alam (2022) research suggested that integrated Social media would be able to add insight as social media usually have the latest "news or issues." Through social media, a new way of life enables multiple perspectives, as marginalized people now have a platform to discuss their needs and life experiences.…”
Section: Resultsmentioning
confidence: 99%
“…As experienced by Solopos in facing the threat of newspaper death caused by the presence of the internet (Suryawati & Alam, 2022). Solopos was able to anticipate this by establishing several online platforms, such as SOLOPOS.com in 2007, radio station SOLOPOS FM in 2004, and a streaming television platform in 2014.…”
Section: Sumber: Datareportalcommentioning
confidence: 99%
“…Kemudian Radar Bandung juga menghasilkan konvergensi teknologi dan jurnalistik, serta kompleksitas dengan mengadopsi scan QR code. (Suryawati & Irawan, 2022) Penelitian (Suryawati & Alam, 2022) berjudul Transformasi Media Cetak ke Platform Digital (Analisis Mediamorfosis Harian SOLOPOS). Penelitian ini menunjukkan bahwa Harian Solopos bertransformasi mendirikan solopos.com.…”
Section: Pendahuluanunclassified